The Acupressure Combination Points BL32 and L14 With Points BL32 And SP6 on Labor Pain in Active Phase - Saadah Mujahidah; Megawati Megawati; Shindi Hapsari (Universitas Karya Husada Semarang, 2022)
ABSTRACTLabor pain that is not resolved will cause hyperventilation so that the need for oxygen increases, blood pressure increases, and reduced intestinal motility and vesikaurinaria. This situation stimulates an increase in catecholamines which disrupts uterine contractions resulting in uterine inertia. Labor pain due to psychic responses and physical reflexes. Acupressure is used to treat pain. Acupressure can affect the intensity of pain. This study was to determine the effect of giving Acupressure Combination of Points BL32-L14 with BL32-Sp6 on Active Phase I Labor Pain in PMB Sukatmi Setrokalangan Kudus. This type of research was a Quasy experiment with a two-group pre-post test design. The sampling technique used was accidental sampling with a sample size of 24 respondents divided into two groups (12 interventions and 12 controls). The normality test used the Shapiro-Wilk test, data analysis used the Wilcoxon and Mann-Whitney tests. Acupressure BL32 and L14 for pain (p 0.03), Acupressure BL32 and Sp6 got p 0.002. Comparison of BL 32-Li4 acupressure with Bl32-Sp6 got p 0.590. There is an effect of Acupressure BL32 and L14 on labor pain, and there is an effect of Acupressure BL32 and Sp6 on labor pain. There was no difference between BL 32-Li4 and Bl32-Sp6 on labor pain. Keywords : acupressure; active phase; bl32-li4; bl32-sp6; labor pain ABSTRAKNyeri persalinan yang tidak teratasi akan menyebabkan hiperventilasi sehingga kebutuhan oksigen meningkat, tekanan darah meningkat, dan motilitas usus berkurang dan vesikaurinaria. Keadaan ini merangsang peningkatan katekolamin yang mengganggu kontraksi uterus sehingga terjadi inersia uterus. Nyeri persalinan karena respon psikis dan refleks fisik. Akupresur digunakan untuk mengobati rasa sakit. Akupresur dapat mempengaruhi intensitas nyeri. Penelitian ditujukan untuk mengetahui pengaruh pemberian Akupresur Kombinasi Titik BL32-L14 dengan BL32-Sp6 terhadap Nyeri Persalinan Aktif Fase I di PMB Sukatmi Setrokalangan Kudus. Jenis penelitian ini adalah Quasy eksperimen dengan desain two-group pre-post test design. Teknik pengambilan sampel yang digunakan adalah accidental sampling dengan jumlah sampel 24 responden yang terbagi menjadi dua kelompok (12 intervensi dan 12 kontrol). Uji normalitas menggunakan uji Shapiro-Wilk, analisis data menggunakan uji Wilcoxon dan Mann-Whitney. Akupresur BL32 dan L14 untuk nyeri (p 0,03), Akupresur BL32 dan Sp6 didapatkan p 0,002. Perbandingan akupresur BL 32-Li4 dengan Bl32-Sp6 didapat p 0,590. Ada pengaruh Akupresur BL32 dan L14 terhadap nyeri persalinan, dan ada pengaruh Akupresur BL32 dan Sp6 terhadap nyeri persalinan. Tidak ada perbedaan antara BL 32-Li4 dan Bl32-Sp6 pada nyeri persalinan. Kata kunci : akupresur; fase aktif; bl32-li4; bl32-sp6; nyeri persalinan